The effect of the mathematics instruction model on enhancing mathematical thinking - Iamcham, Narunat; Chanchusakun, Saranya (Institute of Advanced Engineering and Science, 2024)
The objectives of this research were to study the efficacy of the mathematics instructional model (BRIGHT model) based on realistic mathematics education (RME) and model-eliciting activities (MEAs) approaches to enhance mathematical thinking (MT) for upper primary school students as follows: i) to compare the mathematics achievement of students before and after studying with the BRIGHT model, ii) to compare the MT of students before and after studying with the BRIGHT model, and iii) to evaluate the students' and mathematic teachers' satisfaction on learning activities by using the BRIGHT model. The results of this research were as follows: i) the mathematics achievement and MT of students after studying were significantly higher than before studying with the BRIGHT model; ii) the student satisfaction with learning activities using the BRIGHT model was satisfied all aspects of the assessment. The mean scores from highest to lowest were as follows: benefits that student received, learning atmosphere, and learning activities, respectively; and iii) the satisfaction teachers and educational superiors were very satisfied with the learning management process and applying the BRIGHT model. Therefore, learning through the BRIGHT mathematical modeling has shown all aspects of students' and mathematic teachers' expected development.